2016
DOI: 10.1158/1940-6207.capr-15-0165
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Pubertal Exposure to Dietary Soy on Estrogen Receptor Activity in the Breast of Cynomolgus Macaques

Abstract: Endogenous estrogens influence mammary gland development during puberty and breast cancer risk during adulthood. Early-life exposure to dietary or environmental estrogens may alter estrogen-mediated processes. Soy foods contain phytoestrogenic isoflavones (IFs), which have mixed estrogen agonist/antagonist properties. Here, we evaluated mammary gland responses over time in pubertal female cynomolgus macaques fed diets containing either casein/lactalbumin (n=12) or soy protein containing a human-equivalent dose… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 53 publications
0
9
1
Order By: Relevance
“…age-independent) methylation differences in the adult female population due to soy consumption. However, whereas our analyses indicate no large, age-independent differences in breast methylation, recent literature links the possible positive or negative effect of soy consumption on breast cancer risk in adults to the period or age when soy consumption started 4 , 28 . Early-life exposure to soy may alter estrogen mediated processes and therefore, alter the effect of genistein, daidzein and other isoflavones, which are estrogen antagonists.…”
Section: Discussioncontrasting
confidence: 96%
See 1 more Smart Citation
“…age-independent) methylation differences in the adult female population due to soy consumption. However, whereas our analyses indicate no large, age-independent differences in breast methylation, recent literature links the possible positive or negative effect of soy consumption on breast cancer risk in adults to the period or age when soy consumption started 4 , 28 . Early-life exposure to soy may alter estrogen mediated processes and therefore, alter the effect of genistein, daidzein and other isoflavones, which are estrogen antagonists.…”
Section: Discussioncontrasting
confidence: 96%
“…Early-life exposure to soy may alter estrogen mediated processes and therefore, alter the effect of genistein, daidzein and other isoflavones, which are estrogen antagonists. Whether this effect is sustained by DNA methylation remains largely unknown 28 . Note that also other sources of heterogeneity (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Comparison of the 500 most highly expressed genes in breast tissue from ADOL and in post-pubertal/young adult mice [30] revealed that < 30% of genes overlapped. We expanded this comparative analysis to other existing genomic datasets: (1) RNA-seq data in GTEx from breast tissue samples in 52 adult women and (2) microarray data in GEO from mammary tissue in control or vehicle-treated post-pubertal macaques (7-12 months post-menarche) [31] and young adult rats (age 6-9 weeks) [32] (Additional File 1: Table S5). The adult women were 39.2 ± 8.6 years old (range 21-49), the majority (84.6%) were non-Hispanic Caucasian, and 34.6% were OB (mean BMI for cohort 26.4 ± 4.1 kg/m 2 , range 18.5-35.0), and the majority reported tobacco smoking and/or drinking.…”
Section: Breast Whole Transcriptome Profiles During Adolescence: Younmentioning
confidence: 99%
“…However, in a study starting before menarche of pubertal female cynomolgus monkeys receiving a soy-protein enriched diet (corresponding to a human-equivalent dose of 120 mg isoflavones per day, expressed as aglycone equivalents) for approximately 4.5 years, only a subtle effect of the soy diet on breast differentiation and ER activity was observed. The authors discussed that even this modest change might dampen estrogen responsiveness in the breast tissue later in adulthood (Dewi et al 2013 , 2016 ). This decrease in estrogen responsiveness was also observed in the mammary gland of adult rats, which were exposed pre-/peripubertally or life-long to an isoflavone-rich diet (Blei et al 2015 ; Molzberger et al 2013 ).…”
Section: Effects Of Isoflavonesmentioning
confidence: 99%